Medindo a predisposição para a tecnologia - Bernardi Junior, Plinio (2008)
There is an expectation that each individual absorb, in a fast and satisfactory way, technological advances so that he/she can take advantage of their benefits and remain competitive in the job market. Although the main focus of most researches is on the technological benefits for businesses using technology, the behavior intention of the individual represents the first step towards its adoption. However, at the same time, technology is perceived as an evolution for the benefit of people, there are also clear signs towards a sense of frustration with technology. No study is conclusive about identification of variables that affect the development of perceptions and intentions toward technology. Moreover, most of the models were tested in developed countries or in high social level populations. The main purpose of this thesis is to present an alternative way of measuring the Technology Predisposition, which applies not only in specific situations, but also for the full range of population. This study work makes use of the tools of Item Response Theory, for proposition and validation of a new scale of Technology Predisposition, which proved to be quite consistent and coherent. The new scale has the advantage of having more discriminative power, especially for the lower classes of educational level and income. Moreover, the created scale displays more information with a limited number of items, which may represent cost and time reductions.